2018
DOI: 10.1002/jso.25255
|View full text |Cite
|
Sign up to set email alerts
|

Virtual planning and navigational technology in reconstructive surgery

Abstract: Reconstructive technologies have expanded to include the use of virtual surgical planning (VSP) and computer-aided design and manufacturing (CAD-CAM), and 3-Dimensional printing. The advantages of VSP over traditional techniques are highlighted in many scenarios: (a) delayed reconstruction, (b) maxillary reconstruction, (c) placement of dental implants, and (d) precision guided oncology. Microsurgery is undergoing a paradigm shift with virtual planning at its foreground. Herein, we describe the versatile uses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 17 publications
1
50
0
Order By: Relevance
“…It suggests that VR environment may offer more measurement accuracy of complex anatomical structures with less measurement and identification errors even for experienced surgeons. This is in accordance to previous clinical studies mainly done in reconstructive surgery, which have shown that VR planning improve the accuracy of the surgical outcomes [22,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…It suggests that VR environment may offer more measurement accuracy of complex anatomical structures with less measurement and identification errors even for experienced surgeons. This is in accordance to previous clinical studies mainly done in reconstructive surgery, which have shown that VR planning improve the accuracy of the surgical outcomes [22,23,[28][29][30][31].…”
Section: Discussionsupporting
confidence: 92%
“…Virtual surgical planning has been invaluable for head and neck reconstruction, particularly for maxillary and delayed reconstructions, allowing for precise and efficient tumor resection and reconstruction. Multiple segment osteocutaneous flaps can be crafted in complicated three-dimensional patterns with precision, allowing for improvements in the outcomes and the ability to tackle more challenging problems (Hanasono et al 2010, Stranix et al 2019, Shenaq and Matros 2018.…”
Section: Learning Pointsmentioning
confidence: 99%
“…3D printing technique instruct plate assisted hollow screw fixation for unstable pelvic fractures.3. Application in the treatment of ankle fracture, segmental bone defect, orthosis, orthopedic and reconstruction.Plastic surgery [44,45]1. Aiding the surgery planning for silicone implants that aim to correct the thoracic deformities caused by Polish syndrome.2.…”
Section: Digital Imaging Technologymentioning
confidence: 99%